Zebrafish gbx1 refines the Midbrain-Hindbrain Boundary border and mediates the Wnt8 posteriorization signal - Rhinn, Muriel (BioMed Central, 2009)
BACKGROUND: Studies in mouse, Xenopus and chicken have shown that Otx2 and Gbx2 expression domains are fundamental for positioning the midbrain-hindbrain boundary (MHB) organizer. Of the two zebrafish gbx genes, gbx1 is a likely candidate to participate in this event because its early expression is similar to that reported for Gbx2 in other species. Zebrafish gbx2, on the other hand, acts relatively late at the MHB. To investigate the function of zebrafish gbx1 within the early neural plate, we used a combination of gain- and loss-of-function experiments. RESULTS: We found that ectopic gbx1 expression in the anterior neural plate reduces forebrain and midbrain, represses otx2 expression and repositions the MHB to a more anterior position at the new gbx1/otx2 border. In the case of gbx1 loss-of-function, the initially robust otx2 domain shifts slightly posterior at a given stage (70% epiboly), as does MHB marker expression. We further found that ectopic juxtaposition of otx2 and gbx1 leads to ectopic activation of MHB markers fgf8, pax2.1 and eng2. This indicates that, in zebrafish, an interaction between otx2 and gbx1 determines the site of MHB development. Our work also highlights a novel requirement for gbx1 in hindbrain development. Using cell-tracing experiments, gbx1 was found to cell-autonomously transform anterior neural tissue into posterior. Previous studies have shown that gbx1 is a target of Wnt8 graded activity in the early neural plate. Consistent with this, we show that gbx1 can partially restore hindbrain patterning in cases of Wnt8 loss-of-function. We propose that in addition to its role at the MHB, gbx1 acts at the transcriptional level to mediate Wnt8 posteriorizing signals that pattern the developing hindbrain. CONCLUSION: Our results provide evidence that zebrafish gbx1 is involved in positioning the MHB in the early neural plate by refining the otx2 expression domain. In addition to its role in MHB formation, we have shown that gbx1 is a novel mediator of Wnt8 signaling during hindbrain patterning.